MicroRNA therapy for infected wounds - Hiebert, Paul (EMBO Mol Med, 2018)
A novel approach for identification of functional miRNAs in skin wounds reveals miR‐223 as a key regulator of inflammation during tissue repair. The findings suggest targeting of miR‐233 as an effective strategy to enhance neutrophil activation after bacterial infection and to improve healing of infected wounds.